Teachers’ knowledge and attitudes on dentoalveolar trauma: insights from Samarinda, Indonesia - Nisrina Dwi Cahyarini; Cristiani Nadya Pramasari; Novelin Yohana Ompusunggu; Syahril Samad; Imran Irsal (Dental Journal (Majalah Kedokteran Gigi), 2026)
Background: Dentoalveolar trauma is one of the most common oral traumas. The peak incidence of dentoalveolar trauma is in the permanent teeth of boys aged 8-10 years while playing and exercising at school and affects mixed dentition period. Correct and immediate first-aid dentoalveolar trauma management in school will increase the prognosis of the tooth. Purpose: The study aimed to analyze the relationship between knowledge and attitudes toward the first-aid management of dentoalveolar trauma by elementary school teachers in Samarinda City. Methods: This analytical survey study used a cross-sectional approach, which was conducted in 35 public and private elementary schools in Samarinda City, Indonesia. Independent T-test, analysis of variance (ANOVA), and Pearson correlation were performed to determine the relationship between knowledge and attitudes. Accordingly, the tests assessed the variables of teacher gender, teaching field, teaching experience, and history of receiving information on early management of dentoalveolar trauma. Results: The majority of the teacher’s knowledge and attitudes scores were moderate. There was a significant weak positive correlation between knowledge and attitudes and the first-aid management of dentoalveolar trauma in elementary school teachers in Samarinda (p = 0.000; p<0.05; r = 0.191). In addition, another significant relationship was found between attitudes score and gender (p = 0.02; p<0.05) and teaching experience (in years) of teachers (p = 0.008; p<0.05) in Samarinda. Conclusion: Elementary school teachers in Samarinda City who have a greater understanding of how to manage dentoalveolar trauma also have more positive attitudes towards managing such injuries.